COMPOSITION GAPS, CRITICAL CRYSTALLINITY, AND FRACTIONAL CRYSTALLIZATION IN OROGENIC (CALC-ALKALINE) MAGMATIC SYSTEMS - Brophy J.G. (My University, 1991)
The recognition of a three-way correlation between magmatic SiO2 content, critical crystallinity, and the size (magnitude) of crystal fractionation-generated composition gaps in calc-alkaline magmatic systems suggests an important control of magmatic critical crystallinity on the formation of such composition gaps. To explain this correlation, it is proposed that fractionation-generated composition gaps are caused by: (1) simultaneous interior (i.e. non-substrate) crystallization and vigorous chamberwide convection which leads to progessive crystal suspension; (2) cessation of convection when the percentage of suspended crystals reaches the critical crystallinity of the magma, and; (3) eventual buoyancy-driven crystal-liquid segregation producing a discrete body of fractionated magma which is separated from the initial magma by a composition gap. This mechanism implies that many, if not most magma bodies are characterized by interior crystallization and vigorous convection, conditions which are not universally agreed upon at present. Given that such conditions characterize natural magma bodies, fractional crystallization through crystal settling in low-velocity boundary layers should be an important mechanism of fractional crystallization. In a crystallizing and convecting body of magma, composition gap formation should represent one endmember of a complete spectrum of possible evolutionary paths governed by the relative rates of crystal settling and crystal retention. As a given volcanic plumbing system matures with time, average settling/retention ratios within individual magma bodies should increase due to higher average wall-rock temperatures. It follows that, within a given volcanic center, early-stage volcanism should be more likely to display fractionation-generated composition gaps than later-stage volcanism. Such a temporal evolution has been documented at at least two Aleutian calc-alkaline volcanic centers.